Community-based child health nurses: An exploration of current practice - Borrow, S.; Munns, Ailsa; Henderson, Saraswathy (eContent Management, 2011)
The purpose of this research was to define, the practice domain of community-based child health nursing in light of widespread political, economic and social changes in Western Australia. The project was conducted by a group of nurse researchers with experience in child health nursing from the School of Nursing and Midwifery at Curtin University and the Child and Adolescent Community Health Division at the Department of Health, Western Australia. The overall aim of the project was to map the scope of nursing practice in the community child health setting in Western Australia and to identify the decision making framework that underpins this nursing specialty. Given the widespread social, economic and health service management changes, it was important for nurses involved with, or contemplating a career in, community-based child health to have the role accurately defined. In addition, consumer expectations of the service needed to be explored within the current climate.A descriptive qualitative study was used for this project. A purposive sample of 60 participants was drawn from the pool of child health nurses in the South Metropolitan Community Health Service, North Metropolitan Health Service and Western Australian Country Health Service. Following ethical approval data was collected via participants keeping a 2-week work diary. The data was coded and thematic analysis was applied. Several themes emerged from the analysis which were validated by follow up focus group interviews with participants. This clearly demonstrated common, recurring issues. The results identified that the community-based child health nurses are currently undertaking a more complex and expanded child health service role for an increasingly diverse client population, over their traditional practices which are still maintained. Excessive workloads and lack of human and non human resources also presented challenges. There are increasing requirements for child health nurses to engage in community development and capacity building, often through a multidisciplinary partnership, which requires them to have sound brokerage and facilitation skills to enable community inclusion and inter-agency collaboration at the local level.The study has highlighted the importance and multifaceted nature of the role of the community-based child health nurse. To enable them to function optimally, the following suggestions/recommendations are offered. These being: More physical resources be allocated to community-based child health nursing, More resources allocated to assist community-based child health nurses to support culturally and linguistically diverse families, Mapping of child health nurses' workloads, The development of community health client dependency rating criteria reflecting the social determinants of health in order for health service refinement of staffing allocations based on an acuity scale, Specific staff development opportunities to reflect the increased workload complexity, Managerial support for the implementation of formal clinical (reflective) supervision, Additional clerical assistance with non-nursing duties.